Comparing the Efficacy of Intralesional Combination of Verapamil and Triamcinolone Vs Intralesional Triamcinolone for Treatment of Keloid - Iqbal, Muhammad Tayyab; Khan, Qamar Uddin; Mazhar, Hina; Malik, Asma; Shaukat, Madeeha; Shahid, Muhammad Farhan (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare intralesional combination of verapamil with triamcinolone versus intralesional triamcinolone for resolution of keloid in terms of mean change in Vancouver Scar Scale (VSS).Study Design: Randomized Controlled Trial (Trial Registration: TCTR20251117012)Place and Duration of Study: Departments of Dermatology, Pakistan Emirates Military Hospital (PEMH), and Combined Military Hospital (CMH), Rawalpindi, Pakistan, from Feb to Aug 2025.Methodology: This study included 60 patients, 30 in each group, with diagnosis of keloid and hypertrophic scars where Group-A received combined injection of triamcinolone acetonide (TAC) (20mg/ml) and verapamil (1.25mg/ml), while Group-B received only injection of TAC 20 mg/ml, at three weeks interval for maximum five sessions. After five sessions, keloid scars were assessed by VSS.Results: The study participants had an mean age of 32.58 ± 8.09 years with an mean duration of symptoms lasting 8.27 ± 2.50 months and mean baseline VSS score of 8.48 ± 2.39. Demographic distribution showed 51.70% male and 48.30% female participation. There were no remarkable differences between the groups regarding age distribution, gender, duration of keloids or baseline VSS score. After treatment, the VSS scores were significantly reduced in Group-A (3.37 ± 1.96) compared to Group-B (5.77 ± 2.40) where p